2009
DOI: 10.4028/www.scientific.net/amr.79-82.867
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochromic Properties of Mesoporous WO<sub>3</sub> Film

Abstract: The WO3 film was prepared by dip coating method with WCl6 as the soure of tungsten and P123 as the structure-directing agent. The crystalline phase and microstructure of the film were characterized through XRD and TEM techniques, respectively. It was found the film annealed at 300°C for 4h mainly was amorphous WO3 with a little monoclinic WO3. The TEM micrographs revealed the film was partly ordered mesoporous and the mean pore diameter was about 5nm. The measurements of the cyclic voltammetry suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The aforementioned cracks and pores increase the transmission of H and O while improving the heat resistance. On the basis of the TEM images shown in Figure c,d, after P123 removal many pores ranging from 10 to 16 nm in size remain, which are slightly larger than the 5–8 nm pores reported in the literature. Compared to conventional high-temperature annealing, the WO 3 photocatalytic degradation method to remove the template does not produce pore collapse at high temperatures, so the pore size is slightly larger. Schuster et al conducted an in situ study on synthetic mesoporous materials employing small-angle X-ray scattering (SAXS) technology and found that only the ordered mesoporous structure could be observed after heating and curing for a certain period .…”
Section: Resultsmentioning
confidence: 85%
“…The aforementioned cracks and pores increase the transmission of H and O while improving the heat resistance. On the basis of the TEM images shown in Figure c,d, after P123 removal many pores ranging from 10 to 16 nm in size remain, which are slightly larger than the 5–8 nm pores reported in the literature. Compared to conventional high-temperature annealing, the WO 3 photocatalytic degradation method to remove the template does not produce pore collapse at high temperatures, so the pore size is slightly larger. Schuster et al conducted an in situ study on synthetic mesoporous materials employing small-angle X-ray scattering (SAXS) technology and found that only the ordered mesoporous structure could be observed after heating and curing for a certain period .…”
Section: Resultsmentioning
confidence: 85%
“…Fig. 2 includes sol compositions previously reported in the literature for this chemistry [8,[35][36][37]. Though none of these studies reported on the sensitivity to sol composition, presumably there was some level of optimization and these points provided guidance for the present study.…”
Section: Introductionmentioning
confidence: 92%